Ambulatory assessment of colonic motility using the electromagnetic capsule tracking system. Issue 2 (20th August 2018) - Mark, Esben Bolvig; Poulsen, Jakob Lykke; Haase, Anne‐Mette; Espersen, Marie; Gregersen, Tine; Schlageter, Vincent; Scott, S. Mark; Krogh, Klaus; Drewes, Asbjørn Mohr
Abstract: Background: The Motilis 3D‐Transit system tracks electromagnetic capsules as they traverse the gastrointestinal tract. The method is minimally invasive and ambulatory. Analysis has previously been limited to regional gut transit times, but new methods may allow detailed analysis of colonic motility. Methods: Parameters of colonic motility were analyzed from 34 3D‐Transit recordings performed in healthy volunteers (median age 28 years; 8 F). Characteristic propulsive velocities and lengths of movement were determined to quantify common movement patterns. Data from seven patients with severe chronic diarrhea were included for comparison. Key Results: Lack of capsule motion accounted for 82% (75%‐87%) of total colonic transit time. Propulsive velocities were distributed with peaks at 0.5 cm/min (antegrade or retrograde) and 50 cm/min (antegrade). Based on velocity and length of propagation, five motor patterns were identified; (a) long fast antegrade, (b) fast antegrade, (c) slow antegrade, (d) slow retrograde, and (e) fast retrograde movements. Long fast antegrade movements were median 21 cm (10‐96 cm). Capsule progression was faster during daytime than at night (5.9 cm/h vs 0.8 cm/h; P < 0.01). Colonic transit was faster in patients with chronic diarrhea than in healthy volunteers (5.4 h vs 18.2 h; P = 0.04), with higher capsule velocity (20.4 cm/h vs 4.4 cm/h; P < 0.01). Conclusions and Inferences: The 3D‐Transit system now allows detailed description of colonic motility and our results are supported by those previously suggested by manometry. It holds promise for future assessment of movement patterns to characterize different diseases and effects of treatment. Abstract : The ambulatory Motilis 3D‐Transit system tracks electromagnetic capsules as they traverse the gastrointestinal tract. Parameters of colonic motility were analyzed in recordings from 34 healthy volunteers and seven patients with carcinoid diarrhea.